DEMULSIFICATION OF CUTTING FLUID BEFORE DISPOSAL TO THE ENVIRONMENT (Journal of Engineering, 2010)
In this research the treatment of 7201 cutting fluid was carried out to decrease its environmental impact on water resources after being used and being less effective due to the action of contaminants.The breaking of emulsion was carried out using two methods: The first method was by using acid and/or heat. 1 molar sulfuric acid was used to decrease pH to 1.5 whth heating the emulsion to 90 ºC. It was found that the acid is the dominating factor in emulsion breaking and the maximum efficiency achieved was 85% after one day using (10335 ppm) sulfuric acid. The second method was by using two different types of coagulants calcium chloride (CaCl2) and ferric chloride (FeCl3) at different emulsified oil concentrations (2, 4, 6, 8, 10% by volume.), and the residual oil concentration in water layer was measured for each experiment.It was found that using ferric chloride (FeCl3) gave the best emulsion breaking and least residual oil concentration in water layer for all emulsified oil concentrations.